The New Law and the New Evangelization. The Thomist Tradition and the Moral Perspective of Evangelii Gaudium (Teología, 2015)
The Pope’s pastoral guidelines in Evangelii gaudium offer the opportunity to rediscover the value of the category law under the guidance of the thomistic tradition present in the papal document. The moral proposal of the Gospel or new law, following the synonymy used by Aquinas, cannot be reduced to a precept or a set of rules; quite the contrary, revisiting the doctrine of the Common Doctor, we may discover the need for wisdom and biblical interpretation of the pillars of Christian morality. In the way of pastoral conversion, the return to the thomist sources illuminates theological reflection again with renewed fertility.
Keywords: Moral Law; New Law; System of Laws; Gospel; Holy Spirit; Moral Pneumatology; Grace; Charity; Friendship; usus gratiae; Living and Personal Law; Evangelical Counsels